2021
DOI: 10.3390/cancers13040762
|View full text |Cite
|
Sign up to set email alerts
|

Linking Metabolic Reprogramming, Plasticity and Tumor Progression

Abstract: The specific molecular features of cancer cells that distinguish them from the normal ones are denoted as “hallmarks of cancer”. One of the critical hallmarks of cancer is an altered metabolism which provides tumor cells with energy and structural resources necessary for rapid proliferation. The key feature of a cancer-reprogrammed metabolism is its plasticity, allowing cancer cells to better adapt to various conditions and to oppose different therapies. Furthermore, the alterations of metabolic pathways in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 203 publications
(226 reference statements)
0
27
0
1
Order By: Relevance
“…In general, malignant cells have 1.5-2 times higher MMP levels than their non-malignant counterparts, which is the consequence of an elevated energy metabolism. The level of MMP enhancement is associated with the degree of malignancy of neoplastic cells, including enhanced resistance to aggressive conditions and elevation of their metastatic potential (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, malignant cells have 1.5-2 times higher MMP levels than their non-malignant counterparts, which is the consequence of an elevated energy metabolism. The level of MMP enhancement is associated with the degree of malignancy of neoplastic cells, including enhanced resistance to aggressive conditions and elevation of their metastatic potential (28).…”
Section: Resultsmentioning
confidence: 99%
“…c-Myc and HIF1A are master regulators of metabolic networks. They upregulate and coordinate glycolysis, respiration, one-carbon metabolism, and the metabolism of glutamine and lipids upon tumorigenesis (28,40,41). It is important to note that HIF1A and c-Myc are both known to regulate the expression of tumor-specific isoforms of glycolytic proteins such as GLUT1, HK2, PKM, and LDHA, thereby diminishing the Warburg effect in cancer cells (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…However, notably, the expression of the lipogenic enzymes FASN and ACC are down-regulated in circulating breast cancer cells, which exhibit enhanced mitochondrial respiration that fuels cancer cell motility [ 20 ]. EMT cells undergo oxidative shock upon intravasation of blood cells, followed by attacks from the immune system and requirement of anchorage-independent survival [ 21 ]. Switching their glycolytic metabolism towards a hybrid, more oxidative state would allow them to adapt to the environment, whereupon they find a new metastatic niche [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible contributor to this lower acidification of the TME could be a compensatory mechanism occurring when tumors are treated chronically with an MPC inhibitor. Tumor cells indeed exhibit extraordinary metabolic plasticity to adapt to constraints or changes in their environment [ 6 , 43 , 44 , 45 , 46 ]. It has been previously demonstrated that cells may tolerate loss of MPC activity by metabolic rewiring to compensate for the loss of pyruvate oxidation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%